2011
DOI: 10.1590/s0034-737x2011000200015
|View full text |Cite
|
Sign up to set email alerts
|

Casca de mamona associada a quatro fontes de matéria orgânica para a produção de mudas de pinhão-manso

Abstract: Castor hull combined with four organic matter sources for physic nut seedling productionSubstrates consisting of mixtures of soil and organic materials have usually been recommended for production of physic nut (Jatropha curcas L.) seedlings. Castor hull is a residue produced in large quantities during the hulling process. This residue contains high amounts of macronutrients. The objective of this study was to evaluate four organic materials for mixing with soil and castor hull. The experiment was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
0
7
1
5
Order By: Relevance
“…The maximum growth of the physic nuta plants was observed with the addition of simple superphosphate to the substrate in doses estimated to be in the range 5 to 8 kg m -3 . According to Lima et al (2011b), phosphate fertilizer favored the growth mainly of roots and leaf area. According to the same authors, the addition of phosphate fertilizer provided an increase in plant tissue concentration of all macronutrients, except for calcium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum growth of the physic nuta plants was observed with the addition of simple superphosphate to the substrate in doses estimated to be in the range 5 to 8 kg m -3 . According to Lima et al (2011b), phosphate fertilizer favored the growth mainly of roots and leaf area. According to the same authors, the addition of phosphate fertilizer provided an increase in plant tissue concentration of all macronutrients, except for calcium.…”
Section: Resultsmentioning
confidence: 99%
“…When studying the redistribution of nutrients in physic nut leaves, Lima et al (2011b) found that the levels of K were higher in young leaves with more intense physiological activity, but as these processes reduced, K was redistributed to other plants organs. According to Pacheco et al (2009), the stem, besides being a structural organ of the plant, is a reserve organ.…”
Section: Resultsmentioning
confidence: 99%
“…O pinhão-manso (Jatropha curcas L.) é uma espécie perene pertencente à família das Euforbiáceas, de porte arbustivo e crescimento rápido (Lima et al, 2010), originária da América Central mas se encontra vegetando espontaneamente em diversas regiões do Brasil (Lima et al, 2011). Seu cultivo despertou o interesse econômico após a descoberta do alto teor de óleo apresentado em suas sementes (33 a 38%) o que representa entre 53 e 79% do peso de seus frutos (Dias et al, 2007) e por se tratar de uma planta rústica adaptada a diversas condições edafoclimáticas (Arruda et al, 2004).…”
Section: Introductionunclassified
“…Seu cultivo despertou o interesse econômico após a descoberta do alto teor de óleo apresentado em suas sementes (33 a 38%) o que representa entre 53 e 79% do peso de seus frutos e por se tratar de uma planta rústica adaptada a diversas condições edafoclimáticas (Arruda et al, 2004;Lima et al, 2010;2011).…”
Section: Introductionunclassified